HUWE1 promotes EGFR ubiquitination and degradation to protect against renal tubulointerstitial fibrosis. Issue 3 (4th February 2020) - Zhu, Qian; Dong, Hao; Bukhari, Ashfaq‐Ahmad‐Shah; Zhao, Anran; Li, Min; Sun, Yifei; Zhang, Xue; Cao, Changchun; Su, Dongming; Liang, Xiubin
Abstract: Injury of renal tubular epithelial cells is a key feature of the pathogenicity associated with tubulointerstitial fibrosis and other kidney diseases. HUWE1, an E3 ubiquitin ligase, acts by participating in ubiquitination and degradation of its target proteins. However, the detailed mechanisms by which HUWE1 might regulate fibrosis in renal tubular epithelial cells have not been established. Here, the possible regulation of renal tubulointerstitial fibrosis by HUWE1 was investigated by examining the expression of HUWE1 and EGFR in unilateral ureteral obstruction (UUO) mice. Markedly consistent reciprocal changes in HUWE1 and EGFR expression were observed at the protein and mRNA levels in the kidney after UUO injury. Expression of HUWE1 inhibited TGF‐β‐induced injury to HK‐2 cells, while HUWE1 overexpression decreased the expression of EGFR. Further analysis indicated that HUWE1 physically interacted with EGFR and promoted its ubiquitination and degradation. HUWE1 expression also showed clinical relevance in renal disease, as it notably decreased in multiple types of clinical nephropathy, while EGFR expression significantly increased when compared to the normal kidney. Therefore, this study demonstrated that HUWE1, which serves as an E3 ubiquitin ligase specific for EGFR, promotes EGFR ubiquitination and degradation, thereby regulating EGFR expression and providing protection against kidney injury.